570 Health professionals' role in the humanitarian disarmament movement and preventing armed violence. (1st September 2016) - Valenti, Maria
Abstract : Background: Disarmament and war prevention are now widely perceived as humanitarian goals by governments and non-governmental organisations alike. In recent years, "humanitarian disarmament" campaigns have taken on some of the world's worst weapons, including landmines, cluster munitions, small arms, drones, and nuclear weapons. Description of the problem: An evidence-based awareness of the impact of war and all forms of armed violence on public health, documented by health professionals in hospitals and emergency rooms and conveyed through the stories of the victims and their ravaged communities, has catalysed successful campaigns to prohibit the most inhumane weapons and to impose strict new limits on trafficking in others. While the term is relatively new, humanitarian disarmament has been at the heart of health-based organisations' efforts such as the International Committee of the Red Cross and International Physicians for the Prevention of Nuclear War's work for decades. For example, the medical evidence that nuclear war would be a humanitarian catastrophe to which physicians could organise no meaningful response helped mobilise the international community towards a nuclear test ban and non-proliferation. Results: The health facts about nuclear weapons and the devastation they cause have become the foundation of a Humanitarian Pledge to "stigmatise, prohibit and eliminate nuclear weapons" that, at this writing, has been joined by 117 countries. The human consequences of armed violence has been a central concept in achieving landmark treaties and agreements on conventional weapons including the Mine Ban Treaty, the United Nations Programme of Action on Small Arms and Light Weapons, the Convention on Cluster Munitions and the Arms Trade Treaty. Conclusions: Health organisations and agencies have a key role to play in bringing the humanitarian perspective to the development and implementation of policy instruments and agreements designed to prevent armed violence.